The Moral Behavior Among Nurses in the Government Hospitals in Baghdad (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The nursing profession is associated with irregular working hours, high workload, increasing job demands, and emotional complexity. Nurses may exhibit psychological and physical symptoms due to work-related stress, which sometimes leads to mental health problems more frequently than in individuals working in other professions (Qian et al., 2018, p. 1120).At times, nurses may encounter ethically embarrassing situations in their clinical practices while providing healthcare that conflict with their professional and personal values. The work of some healthcare providers may be inefficient due to regulatory constraints, unsafe working conditions, emergencies, limited resources, and insufficient staffing. These factors lead to difficulties in making ethical decisions in the moral situations faced by nurses, which foster negative feelings, frustration, and stress in daily interactions with patients (Comrie, 2012, p. 116). This leaves little room for considering ethical mindfulness due to the ethical dilemmas and conflicts nurses encounter (Sundelin & Hagberg, 1992, p. 262).